2014
DOI: 10.1186/1479-5868-11-50
|View full text |Cite
|
Sign up to set email alerts
|

Changes to the school food and physical activity environment after guideline implementation in British Columbia, Canada

Abstract: BackgroundHigh rates of childhood obesity have generated interest among policy makers to improve the school food environment and increase students’ levels of physical activity. The purpose of this study was to examine school-level changes associated with implementation of the Food and Beverage Sales in Schools (FBSS) and Daily Physical Activity (DPA) guidelines in British Columbia, Canada.MethodsElementary and middle/high school principals completed a survey on the school food and physical activity environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
31
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 33 publications
3
31
0
1
Order By: Relevance
“…The implementation of school food policy is relevant even in the absence of a state school meal programme. Provincial school food and beverage policies in Canada, for example, have had an impact in terms of reducing the availability of sugarsweetened beverages, French fries and confectionery available within schools (25,26) ; and a 'Healthy School Canteen' initiative in Dutch schools has improved the food environment, healthy eating curriculum and school food policy in the majority of participating schools (27) . For our participants, food from the local environment was as influential as the school setting food because students were accessing both sources equally.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The implementation of school food policy is relevant even in the absence of a state school meal programme. Provincial school food and beverage policies in Canada, for example, have had an impact in terms of reducing the availability of sugarsweetened beverages, French fries and confectionery available within schools (25,26) ; and a 'Healthy School Canteen' initiative in Dutch schools has improved the food environment, healthy eating curriculum and school food policy in the majority of participating schools (27) . For our participants, food from the local environment was as influential as the school setting food because students were accessing both sources equally.…”
Section: Discussionmentioning
confidence: 99%
“…While existing school food research demonstrates the impact different policies and practices have on food environments and student behaviours (22)(23)(24)(25)(26) , cultural differences relating to state and school policies, food environments, food sources and student behaviour norms can preclude the generalisation of findings between countries (12) . To our knowledge, there is no published literature on the dietary choices Irish secondary-school students make in the school context or data to show where they source their school-day foods.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…A study in Minnesota found that access to low-nutrient, energy-dense beverages and snacks decreased from 2002 to 2008 (81). One school found that implementing policies based on guidelines in Canada resulted in the reduction of SSBs and unhealthy foods and wider access to fruits, vegetables, and physical activity (145). However, another study found that students who had in-school access to vending machines had fewer servings of soda and fast food during the week from other sources, indicating that the school food environment is only one of several to which students are exposed throughout the week (133).…”
Section: Limit Access To Sugar-sweetened Beveragesmentioning
confidence: 99%